Isolation of a candidate gene for Menkes disease that encodes a potential heavy metal binding protein. - Chelly, J; Tümer, Z; Tønnesen, T; Petterson, A; Ishikawa-Brush, Y; Tommerup, N; Horn, N; Monaco, A (1993)
Menkes disease is a lethal-X linked recessive disorder associated with copper metabolism disturbance. We have recently mapped two chromosome breakpoints related to this disease in a 1 megabase yeast artificial chromosome contig at Xq13.3. We now report the construction of a phage contig and the isolation of candidate partial cDNAs for the Menkes disease gene. The candidate gene expresses an 8 kb message in all investigated tissues, and deletions were detected in 16% of 100 unrelated Menkes patients. The deduced partial protein sequence shared the GMTCXXC motif with bacterial metal resistance operons, suggesting a potential heavy metal binding protein. These findings should lead to more accurate prenatal diagnosis of this severe disease and a better understanding of the cellular homeostasis of essential heavy metals.